Comparison of different fracture modelling approaches to gravity dam failure. Issue 1 (25th February 2014) - Pan, Jianwen; Feng, Yuntian; Jin, Feng; Zhang, Chuhan; Roger Jones Owen, David
Abstract : Purpose: – There is not a unified modelling approach to finite element failure analysis of concrete dams. Different behaviours of a dam predicted by different fracture methods with various material constitutive models may significantly influence on the dam safety evaluation. The purpose of this paper is to present a general comparative investigation to examine whether the nonlinear responses of concrete dams obtained from different fracture modelling approaches are comparable in terms of crack propagation and failure modes. Design/methodology/approach: – Three fracture modelling approaches, including the extended finite element method with a cohesive law (XFEM-COH), the crack band finite element method with a plastic-damage relation (FEPD), and the Drucker-Prager (DP) elasto-plastic model, are chosen to analyse damage and cracking behaviour of concrete gravity dams under overloading conditions. The failure process and loading capacity of a dam are compared. Findings: – The numerical results indicate that the three approaches are all applicable to predict loading capacity and safety factors of gravity dams. However, both XFEM-COH and FEPD give more reasonable crack propagation and failure modes in comparison with DP. Therefore, when cracking patterns are the major concern for safety evaluation of concrete dams, it is recommended that XFEM-COH and FEPD rather than DP be used. Originality/value: – The comparison of cracking behaviours of concrete dams obtained from different fracture modelling approaches is conducted. The applicability of the modelling approaches for failure analysis of concrete dams is discussed, and from the results presented in this work, it is significant to consider the suitability of the selected fracture modelling approach for dam safety evaluation.